2016
DOI: 10.1002/ecy.1473
|View full text |Cite
|
Sign up to set email alerts
|

Habitat augmentation drives secondary invasion: an experimental approach to determine the mechanism of invasion success

Abstract: The entry of secondary invaders into, or their expansion within, native communities is contingent on the changes wrought by other (primary) invaders. When primary invaders have altered more than one property of the recipient community, standard descriptive and modeling approaches only provide a best guess of the mechanism permitting the secondary invasion. In rainforest on Christmas Island, we conducted a manipulative field experiment to determine the mechanism of invasion success for a community of land snail… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 48 publications
(125 reference statements)
0
5
0
Order By: Relevance
“…Despite being the strongest examples of secondary invasion, only Green et al. () specifically used that term with Grosholz () instead described his findings as an “accelerated invasion.” More examples of secondary invasion as we describe it have been published in recent years, including research on exotic land snails (O'Loughlin & Green, , ), soil seed banks (Gioria, Dieterich, & Osborne, ; Gioria, Jarošík, & Pyšek, ; Gioria & Pyšek, ; Gioria, Pyšek, & Moravcova, ), and invasive plants (Flory & Bauer, ; French, ; Stotz, Gianoli, Patchell, & Cahill, ); however, these are only the studies that have explicitly used the term “secondary invasion” (see Figure ). It is likely that other examples of invader‐facilitated invasion have been published in that time, but our ability to identify them is constrained by the absence of consistent and clear terminology for the phenomenon.…”
Section: Demonstrated Secondary Invasions At Different Stages Of the mentioning
confidence: 99%
See 2 more Smart Citations
“…Despite being the strongest examples of secondary invasion, only Green et al. () specifically used that term with Grosholz () instead described his findings as an “accelerated invasion.” More examples of secondary invasion as we describe it have been published in recent years, including research on exotic land snails (O'Loughlin & Green, , ), soil seed banks (Gioria, Dieterich, & Osborne, ; Gioria, Jarošík, & Pyšek, ; Gioria & Pyšek, ; Gioria, Pyšek, & Moravcova, ), and invasive plants (Flory & Bauer, ; French, ; Stotz, Gianoli, Patchell, & Cahill, ); however, these are only the studies that have explicitly used the term “secondary invasion” (see Figure ). It is likely that other examples of invader‐facilitated invasion have been published in that time, but our ability to identify them is constrained by the absence of consistent and clear terminology for the phenomenon.…”
Section: Demonstrated Secondary Invasions At Different Stages Of the mentioning
confidence: 99%
“…Codium fragile could only establish following the creation of a gap in the kelp forest, mediated by another invasive species growing epiphytically on the kelp (Levin et al., ). Potential invaders may also be inhibited by multiple properties of recipient ecosystems (Cross, ; Morales & Aizen, ; O'Loughlin & Green, ). For example, Morales and Aizen () demonstrated that exotic plants were facilitated directly by increased disturbance and indirectly by increased presence of exotic insect pollinators in disturbed areas.…”
Section: The Mechanisms By Which Primary Invaders May Facilitate Secomentioning
confidence: 99%
See 1 more Smart Citation
“…Since we have studied and examined all shell materials from BORN, MZU, ZMA, RMNH, MFN, NHMUK, and JJV, we find that it is useful to highlight some issues related to the “non-scaly” group that could be beneficial for future understanding. Firstly, the name G.williamsi was mentioned in several publications to refer to a species with distinct spiral ribs (Thompson and Dance 1983; Clements et al 2008; Nurinsiyah et al 2016; Maassen 2003; O’Loughlin and Green 2016; Vermeulen and Whitten 1998). After examination of the holotype of G.williamsi in the NHMUK, we find that this species name has often been misapplied.…”
Section: Resultsmentioning
confidence: 99%
“…We appreciate that for researchers focused on the impacts of invasive plants and their management on native plant communities (e.g., Pearson, Ortega, Runyon, & Butler, ), “secondary invasion” is widely understood to mean where invasive species establish following management intervention of a different invader (what we referred to as “management‐mediated invasion”). However, this is quite different from how others have used the term or even described that same process outside of invasive plant management (e.g., Albaina et al., ; Baldwin, Carpenter, Rury, & Woodward, ; Flory & Bauer, ; Green et al., ; O'Loughlin & Green, ). We maintain that there is no intrinsic common feature that would justify the continued undefined use of “secondary invasion” to simultaneously label multiple and quite dissimilar invasion phenomena (O'Loughlin & Green, ).…”
mentioning
confidence: 78%